Phytocannabinoids and the eye – a systematic review - Wolnik, Anna; Woś, Małgorzata; Mackiewicz, Jerzy (Klinika Oczna / Acta Ophthalmologica Polonica, 2021)
Recently, the use of marihuana for medical purposes has become more common. It can lead to many desired effects within the eye, as well as several adverse ones (i.a.: decrease in intraocular pressure, reduction of corneal pain and suppression of inflammation after chemical injury of cornea, treatment of blepharospasm, reduction of nystagmus, decrease in corneal endothelial cell density, eye irritation). There have not been enough studies with human subjects done on the safety and effectiveness of cannabis use in ophthalmology. Although synthetic cannabinoids combined with modulation of the endocannabinoid system might become the future of ophthalmology, more studies on this topic should be conducted.